A Bioinspired Platform for Effective Delivery of Protein Therapeutics to the Central Nervous System. Issue 18 (25th February 2019) - Wu, Di; Qin, Meng; Xu, Duo; Wang, Lan; Liu, Chaoyong; Ren, Jie; Zhou, George; Chen, Chen; Yang, Fengmei; Li, Yanyan; Zhao, Yuan; Huang, Ruyi; et al.
Abstract: Central nervous system (CNS) diseases are the leading cause of morbidity and mortality; their treatment, however, remains constrained by the blood–brain barrier (BBB) that impedes the access of most therapeutics to the brain. A CNS delivery platform for protein therapeutics, which is achieved by encapsulating the proteins within nanocapsules that contain choline and acetylcholine analogues, is reported herein. Mediated by nicotinic acetylcholine receptors and choline transporters, such nanocapsules can effectively penetrate the BBB and deliver the therapeutics to the CNS, as demonstrated in mice and non‐human primates. This universal platform, in general, enables the delivery of any protein therapeutics of interest to the brain, opening a new avenue for the treatment of CNS diseases. Abstract : A universal central nervous system delivery platform for protein therapeutics is developed, enabling the delivery of any protein therapeutics of interest to the brain via choline transporters and acetylcholine receptors.